2020
DOI: 10.1007/s42452-020-2121-9
|View full text |Cite
|
Sign up to set email alerts
|

Ti doped BaMnO3 perovskite structure as photocatalytic agent for the degradation of noxious air and water pollutants

Abstract: Photocatalytic degradation of noxious water and air impurities like Methylene blue (MB), Rhodamine B (RhB), NO x-, and CO is carried out by pristine and Ti-doped BaMnO 3 (BaMn 0.85 Ti 0.15 O 2.93 , BMT). Perovskite BMT ceramic mixed with equimolar ratio of zeolite is used for investigation of water and air pollutant degradation. The synthesized Ti-doped BaMnO 3 (BaMn 0.85 Ti 0.15 O 2.93 , BMT) perovskite was characterized using X-ray diffraction (XRD) and FE-SEM techniques. The XRD pattern of Ti-doped BaMnO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The redox reaction of the photogenerated electron–hole pair gives reactive species such as (OH*, OH − , H + ), and these reactive species then attack the organic pollutants and degrade them into low molecular weight products (environmentally friendly products) within no time. 153,157,158…”
Section: Perovskite Oxide Based Materialsmentioning
confidence: 99%
“…The redox reaction of the photogenerated electron–hole pair gives reactive species such as (OH*, OH − , H + ), and these reactive species then attack the organic pollutants and degrade them into low molecular weight products (environmentally friendly products) within no time. 153,157,158…”
Section: Perovskite Oxide Based Materialsmentioning
confidence: 99%
“…Moreover, both theoretical analyses and experimental investigations have indicated that the substitution of Mn for the Ti site narrows the band gap of SrTiO3 and limits e − and h + recombination, thereby generating sufficient time to let the photovoltaic holes oxidize the water to form •OH to break down TC [16]. Siddharth Singh et al [17] researched doping Ti into BaMnO3 to decompose toxic impurities in water. It was observed that BaMn0.85Ti0.15O2.93 showed enhanced photocatalytic decomposition (~99%) compared with BaMnO3 for toxic water impurities such as Rhodamine B and Methylene blue dyes within 270 and 150 minutes under natural sunlight.…”
Section: Introductionmentioning
confidence: 99%